Blockade Billy ; Morality - King, Stephen, 1947- (New York : Scribner, 2010)
"Even the most die-hard baseball fans don't know the true story of William "Blockade Billy" Blakely. He may have been the greatest player the game has ever seen, but today no one remembers his name. He was the first--and only-- player to have his existence completely removed from the record books." --from cover.
Keywords: Baseball stories; Murder -- Fiction; Baseball players -- Fiction; Baseball stories; Suspense fiction